ANALISIS PERBANDINGAN RISIKO KERUSAKAN DAN KERUGIAN EKONOMI BANGUNAN RUMAH TINGGAL DAN FASILITAS KESEHATAN AKIBAT GEMPA BUMI DI JAWA BARATâ - Victory
West Java is an area that is prone to earthquakes because it is part of the Pacific Ring of Fire which is active due to the movement of tectonic plates. In West Java, there are several points of earthquake threat, including the Cimandiri Fault, Lembang Fault, and Baribis Fault. Earthquake will cause great damage to infrastructure. Among the infrastructure affected by the earthquake were Residential Buildings and Health Facilities Buildings. This study aims to analyze the risk of damage and economic loss of Residential Buildings and Health Facilities Buildings due to the earthquake in West Java. The method used in this research is the event based probabilistic damage and risk analysis method. The data used in this research are exposure data for residential buildings and health facilities buildings, earthquake hazard model data, vulnerability and fragility data, and data on administrative boundaries for the West Java region to display thematic maps. The calculations were performed using Openquake Engine and QGIS software. From the study, the results of the risk of residential loss are Rp.2.99 trillion and the risk of loss of health facility buildings amounted to Rp.6.9 billion. The risk of damage to residential houses is 0.0057, while the risk of damage to health facilities is 0.0034. From the research, it was also found that the western and southern parts of West Java tend to have a greater risk of damage and economic losses to buildings. This is because the western and southern parts of West Java have greater potential and earthquake shocks. The value of the risk of damage and economic loss of residential buildings and health facilities is influenced by the number of buildings, the taxonomic structure of the building, and the location of the area where the building is located.